Characteristics of Criminal Responsibility for the Participation of Citizens of the Republic of Kazakhstan in Foreign Armed Conflicts - TASKYN, Yernar T.; BIMOLDANOV, Yerzhan M. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018DO - 10.14505//jarle.v9.1(31).37, 2018)
The article examines the characteristics of the participation of citizens of the Republic of Kazakhstan in foreign conflicts as an object of criminal investigation. The mechanisms for the emergence of foreign armed conflicts, as well as the reasons and conditions that facilitate the participation of citizens of the Republic of Kazakhstan, have been examined. In the course of the study of international legislation and international experience in regulating public relations in this area, specific recommendations and methodology for studying of the participation of citizens of the Republic of Kazakhstan in foreign conflicts have been developed as an independent research object. Due to the lack of legal means for bringing persons who took part in fighting abroad to responsibility, the criminal liability of citizens for involvement in armed conflicts in the territory of foreign states was introduced in domestic legislation. The authors of the study identified the public danger of the crime, which meant that citizens of Kazakhstan, when returning to their home country, by acquiring a subversive-terrorist experience, could contribute to the commission of crimes directed against the national security of the Republic of Kazakhstan. According to the findings of the study, successful and effective opposition to the participation of citizens of the Republic of Kazakhstan in foreign conflicts depends largely on the degree of theoretical development of the considered problem.